2021
DOI: 10.3389/fphar.2021.761884
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tissue Distribution, and Human Serum Albumin Binding Properties of Delicaflavone, a Novel Anti-Tumor Candidate

Abstract: Delicaflavone (DF), a natural active ingredient from Selaginella doederleinii Hieron, has been reported to have favorable anticancer effects and is thus considered a potential anticancer agent. However, its pharmacokinetics and plasma protein binding properties remain unknown. Here, we investigated the pharmacokinetic profile of DF in rats using a validated HPLC-MS/MS methods, as well as its human serum albumin (HSA) binding properties through multi-spectroscopic and in silico methods. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Currently, it is still an attention spot for screening natural active ingredients [ 3 , 4 ], especially for anti-cancer candidates from herbal medicines [ 5 ]. Selaginella doederleinii Hieron, an anticancer Chinese herb medicine and belonging to the Selaginella genus of the Selaginellaceae family [ [6] , [7] , [8] ], has been recognized recently as a research topic by researchers due to its anti-cancer potentials [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. According to the reports [ 7 , 8 ], S .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is still an attention spot for screening natural active ingredients [ 3 , 4 ], especially for anti-cancer candidates from herbal medicines [ 5 ]. Selaginella doederleinii Hieron, an anticancer Chinese herb medicine and belonging to the Selaginella genus of the Selaginellaceae family [ [6] , [7] , [8] ], has been recognized recently as a research topic by researchers due to its anti-cancer potentials [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. According to the reports [ 7 , 8 ], S .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of tissue distribution of delicaflavone after intravenous administration has illustrated distribution predominantly in the livers, lungs, and kidneys, followed by rapid elimination. However, to the best of our knowledge, there are no specific reports on the tissue distribution, excretion, and plasma protein binding of TBESD (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The anticancer immunological response mediated by delicaflavone was reversed in tumor-bearing mice by overexpression of the N6-methyladenosine (m6A) transferase Mettl3/Mettl14 [151]. In addition, the pharmacokinetic profile of delicaflavone in rats was also examined by Chen et al [155] using a validated HPLC-MS/MS method, including its binding characteristics to human serum albumin utilizing multispectral and computer simulation approaches. The results showed that delicaflavone was rapidly eliminated after intravenous administration, with wide tissue distribution.…”
Section: In Vivo Studiesmentioning
confidence: 99%